Chronic Insomnia - Bianchi, Matt T. (Seminars in Neurology, 2017)
Insomnia is characterized by difficulty falling asleep or staying asleep, with consequent daytime impairment of mental and/or physical function. A detailed clinical history reveals the relative impact of a variety of different contributing and perpetuating factors, which then informs prioritization among different treatment options. Nonpharmacological approaches, especially the validated approach of cognitive–behavioral therapy for insomnia, are preferred over hypnotic medications. If hypnotics are chosen, the goal is short-term interventions after a careful risk-benefit assessment and shared decision-making with the patient. Although objective testing via polysomnography is not routinely indicated, such investigations can be informative in those at risk for concurrent primary sleep disorders, and in those who are treatment refractory. Circadian rhythm disorders can present with insomnia complaints, but are managed with chronotherapy. Whatever management pathway is pursued, the response to therapy should be anchored in improvements in daytime function.
Keywords: insomnia; hypnotic; phenotyping; polysomnography; cognitive–behavioral therapy